Thermodynamic Hydricity of Small Borane Clusters and Polyhedral closo-Boranes † - Golub, Igor E. (Molecules, 2020)
Thermodynamic hydricity (HDA(MeCN)) determined as Gibbs free energy (ΔG°[H](−)) of the H(−) detachment reaction in acetonitrile (MeCN) was assessed for 144 small borane clusters (up to 5 boron atoms), polyhedral closo-boranes dianions [B(n)H(n)](2−), and their lithium salts Li(2)[B(n)H(n)] (n = 5–17) by DFT method [M06/6-311++G(d,p)] taking into account non-specific solvent effect (SMD model). Thermodynamic hydricity values of diborane B(2)H(6) (HDA(MeCN) = 82.1 kcal/mol) and its dianion [B(2)H(6)](2−) (HDA(MeCN) = 40.9 kcal/mol for Li(2)[B(2)H(6)]) can be selected as border points for the range of borane clusters’ reactivity. Borane clusters with HDA(MeCN) below 41 kcal/mol are strong hydride donors capable of reducing CO(2) (HDA(MeCN) = 44 kcal/mol for HCO(2)(−)), whereas those with HDA(MeCN) over 82 kcal/mol, predominately neutral boranes, are weak hydride donors and less prone to hydride transfer than to proton transfer (e.g., B(2)H(6), B(4)H(10), B(5)H(11), etc.). The HDA(MeCN) values of closo-boranes are found to directly depend on the coordination number of the boron atom from which hydride detachment and stabilization of quasi-borinium cation takes place. In general, the larger the coordination number (CN) of a boron atom, the lower the value of HDA(MeCN).